Heading for the hills? A multi-isotope study of sheep management in first-millennium BC Italy. (February 2020) - Trentacoste, A.; Lightfoot, E.; Le Roux, P.; Buckley, M.; Kansa, S.W.; Esposito, C.; Gleba, M.
Highlights: A multi-isotope pilot study of sheep management in proto-historic Italy. Sheep from an elite 7th-century BC residence were consistent with management in the local hinterland. An Archaic Etruscan city (5th century BC) drew animals from a mosaic of iso-zones. No clear evidence for long-distance vertical transhumance. Abstract: Livestock husbandry played a fundamental role in the economy of ancient Mediterranean communities. In central Italy, archaeological evidence for a significant re-organisation of animal production appears during the first millennium BC alongside the rise of urban settlements and an aristocratic class. Urban sites are interpreted as having a central role in the organisation of agricultural production, through control over their territories and the re-distribution/exchange of agricultural products. However, these hypotheses have never been bio-archaeologically demonstrated. Here, we present a detailed multi-isotope pilot study of sheep management and mobility – the first isotopic study dedicated to fauna from late prehistoric or Roman Italy – which investigates animal management and agricultural provisioning in two Etruscan sites (675–430 BC). We used ZooMS to confirm species identifications, and isotopic analyses ( 87 Sr/ 86 Sr, δ 18 O, δ 13 C, and δ 15 N) to gain insight into differences in animal management at the ancient city of Velzna (5th century BC), modern Orvieto, and the aristocratic residence of Poggio Civitate (7th century BC). Results demonstrate that Orvieto received sheep raised in at least three distinct locations, while data from Poggio Civitate were compatible with herding in a single area. These results reinforce interpretation of Orvieto as a central place that collected resources from its hinterland, while Poggio Civitate employed a more isolated production strategy. Analyses did not produce evidence for long-distance vertical transhumance at either site, with results suggesting more local variation in herding patterns, consistent with seasonal herding in the general hinterland of each location. This pilot study offers a first step towards higher-resolution understanding of animal management in the region, and demonstrates the potential of further isotopic studies to provide new insights on agricultural provisioning and territorial control in proto-historic Italy.